Specifications study of Hydrophobic Silica Aerogel Doped with Rhodamine 6G Prepared via Sub-Critical Drying Technique - AL-Sharuee, Israa F. (Iraqi Journal of Science, 2021)
The influence of dye laser Rhodamine 6G (R6G) on the molecular structure of silica aerogel prepared by normal drying method is reported. The study also tests the effect of dye concentration on morphological and physical properties. Fourier Transform Infrared Spectroscopy (FTIR) was used to examine this effect, in addition to Field Emission Scanning Electron Microscopy (FESEM), contact angle, and surface area measurement. It was found from FTIR data that the dye laser stays with the inner structure of samples and, at high concentration, it gives a good influence by reducing (OH) band and increasing (CH) band, leading to changing the contact angle from (123á´¼) to (145á´¼). Whereas particle size varied from 22 nm to 47 nm after doping, resulting in a decrease in surface area from 673 m2/gm before doping to 357 m2/gm after doping. It was also found that the samples became lightweighted through the noticeable decrease in the amount of density from 0.28 to 0.17 gm/cm3.